INTEGRATED OFFICE WASTE MANAGEMENT - Shochib, Rosita (BPPT)
Municipal waste from day to day has increased its production in line with the increase of urban population. However, running a waste management system has been unable to solve the problem of waste properly. Therefore, a new breakthrough is needed to deal with. With the enactment of Law No. 18 of 2008 on Waste Management, each source must be to reduce the amount of waste to be disposed of to the final processing of waste. The office is one of the sources of waste, also must reduce the amount of waste that must be disposed of to the final processing of waste (landfill). The purpose of this paper is to examine waste management in an integrated manner to maximize the waste management office. In the process of management, garbage collector used by officers in the study. The rest moved to the TPS waste. In this place officers also collect that is still valuable economic and processed organic waste into compost. Of these operations, the rest of office waste disposed to landfill about 48.7%keywords : office waste, integreted office waste management